Does expanding fiscal space lead to improved funding of the health sector in developing countries?: lessons from Kenya, Lagos State (Nigeria) and South Africa - Jane Doherty; Doris Kirigia; Chijioke Okoli; Jane Chuma; N Ezumah; Hyacinth Ichoku; Kara Hanson; Diane McIntyre (Taylor & Francis Group, 2018)
Background: The global focus on promoting Universal Health Coverage has drawn attention to the need to increase public domestic funding for health care in low- and middle-income countries. Objectives: This article examines whether increased tax revenue in the three territories of Kenya, Lagos State (Nigeria) and South Africa was accompanied by improved resource allocation to their public health sectors, and explores the reasons underlying the observed trends. Methods: Three case studies were conducted by different research teams using a common mixed methods approach. Quantitative data were extracted from official government financial reports and used to describe trends in general tax revenue, total government expenditure and government spending on the health sector and other sectors in the first decade of this century. Twenty-seven key informant interviews with officials in Ministries of Health and Finance were used to explore the contextual factors, actors and processes accounting for the observed trends. A thematic content analysis allowed this qualitative information to be compared and contrasted between territories. Findings: Increased tax revenue led to absolute increases in public health spending in all three territories, but not necessarily in real per capita terms. However, in each of the territories, the percentage of the government budget allocated to health declined for much of the period under review. Factors contributing to this trend include: inter-sectoral competition in priority setting; the extent of fiscal federalism; the Ministry of Finance's perception of the health sector's absorptive capacity; weak investment cases made by the Ministry of Health; and weak parliamentary and civil society involvement. Conclusion: Despite dramatic improvements in tax revenue collection, fiscal space for health in the three territories did not improve. Ministries of Health must strengthen their ability to motivate for larger allocations from government revenue through demonstrating improved performance and the relative benefits of health investments.